Psychometric Properties of the Computer Self-Efficacy Scale for EXANI-II - Martínez Pineda, José Antonio (REDIE es una publicación del Instituto de Investigación y Desarrollo Educativo (IIDE)., 2014)
The impact of Information and Communication Technologies on students’ academic performance has been studied from many perspectives, including computer self-efficacy scales (CSE), which have been used as predictors of students’ knowledge and real-world skills (Johnson, 2005; Marakas, Johnson and Clay, 2007). The aim of this study was the analysis of the psychometric properties of a CSE scale and its association with performance on the National Entrance Examination for Higher Education (EXANI-II). Results on a national sample (n = 548756) suggest that the scale has good reliability (α=.92), acceptable fit indicators (RMSEA =.05, CFI = .96) and statistically significant association (r=.346) with performance on the EXANI-II. Findings confirm the relevance of CSE as a predictor of academic performance.